Clinical and epidemiological features of A H1N1 Influenza in Almanzor Aguinaga Asenjo National Hospital - Díaz Vélez, Cristian (2010)
Objective: To know the epidemiological and clinical features in confirmed cases of A H1N1 influenza in patients treated between July 2009 and February 2010 in Almanzor Aguinaga Asenjo National Hospital - ESSALUD, Lambayeque Healthcare Network.   Material and method: This is a cross-sectional descriptive study performed in 212 patients with a confirmed diagnosis of A H1N1influenza. We used a previously structured and coded data collection form, we reviewed clinical and epidemiological records of each patient, and data analysis was performed using Excel software.   Results: Male subjects were slightly more frequently affected; 59% (125) of patients were children (mean age: 19.7 ± 18.9 years; median, 12 years), the age group between 5- to 14- years was most frequently affected with 44% (92), followed by the 15- to 44- years group (27.8%, 59 patients). In male patients, the highest number of reported cases was found in the 10- to 14- years age group (27 cases), followed by the 5- to 9- years group (27 cases) and the 0- to 4- years (15 cases); when combining male and female patients, the most frequently affected age groups were those patients 5- to 9- years old (24 cases), followed by subjects 10- to 14- years old (14 cases) and those 0- to 4- years old (08 cases). With respect to their living places, most cases (45%) came from Chiclayo District, followed by Pomalca (9.9%), José Leonardo Ortiz (8.49%), and La Victoria (4.72%) districts. Confirmed cases were concentrated between 28th and 33rd epidemiological weeks, and there were periods during which no cases were reported (epidemiological weeks 43, 44, 45, 48, 51 and 52). 54.5% of confirmed cases were admitted from an outpatient clinic called Unidad de Influenza, 33.4% came from the emergency service. One-third (33.5%) of the latter patients required hospitalization and 1.4% were admitted to the ICU. Most frequently found signs and symptoms were fever, cough, runny nose, sore throat, and malaise, the first 3 were present in 87.3% of cases (84.4% in children and 90.8% in adults). Eleven patients died, 4 of them were young adults, who reported no comorbidities. The mortality rate was higher in adults (9.19 x 100 confirmed cases), the attack rate was higher in the 5- to 14- year old group, 141.33 x 100,000, followed by children under 5 years, who showed a 109.86 x 100,000 rate R. The longest average hospital stay was found in the 45-to 64- years old age group, 8 days, followed by the 5- to 14- years old age group. Patients who developed complications and who were admitted in the ICU had disease duration times 3.64 ± 1.66 and 5.0 ± 2.0 days, respectively and their hospital stay was 6.35 ± 6.56 and 12.31 ± 8.99 days.   Conclusions: Almost half of the patients with a confirmed diagnosis of A H11 influenza treated in our hospital were children, male, and most reported having contact with persons with respiratory symptoms within seven days prior to the onset of symptoms, most subjects were treated in the outpatient clinic, and morbidity and hospitalization rated were higher in 5-14- year old children. The mean duration of the disease was higher in those admitted to the ICU or in those who presented with complications, and the average hospital stay was longest in the 45- to 64- years old group.